Analisis Pendapatan Usahatani Dan Pengolahan Sereh Wangi Pada Rumah Atsiri Lookena Kelurahan Tataaran II Kecamatan Tondano Selatan Kabupaten Minahasa: Analysis of Farming Income and Processing of Fragrant Citronella at Lookena Essential House, Tataaran II Village, South Tondano District, Minahasa Regency - Lampus, Juan Daniel; Ngangi, Charles Reijnaldo; Loho, Agnes Estephina (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
The aim of this research is to calculate maintenance costs and refining costs for citronella citronella. This research will be carried out from preparation to completion for 3 months from January 2023 to March 2023. The data used in this study were primary data obtained from citronella farmers, namely related to cost, price, number of farmers, citronella cultivation process, while secondary data was obtained from the Central Bureau of Statistics and agencies related to this research. Data collection techniques carried out in this study used interviews, observation and literary/library methods. The results in the research, citronella farming at Atsiru "Lookena" house in Tataaran Village, Tondano Selatan District, Minahasa Regency, generates a significant income of IDR 15,000,000 per hectare with a net income of IDR 7,018,400 per hectare in one harvest season. Although the success of this farming can be influenced by factors such as air humidity, harvested area, rainfall, and changing selling prices, with good management, citronella farming can be a profitable business with high profit potential.